Loss to follow-up in tuberculosis treatment and its relationship with patients' knowledge of the disease and other associated factors (2016)
Objective To identify factors associated with loss to follow-up in Tuberculosis (TB) treatment, including patients' level of knowledge regarding treatment of this disease.Methods 42 loss to follow-up cases and 84 control cases that were finishing the sixth month of their first treatment for tuberculosis were selected for this study. Primary data were gathered through interviews, while secondary data were obtained from the notification form of the disease, between December 2011 and April 2012. Factors associated with loss to follow-up were analyzed by means of a conditional logistic regression multivariate model for matched case-control groups.Results No significant differences were observed between loss to follow-up cases and controls regarding socioeconomic factors, lifestyle, clinical condition, treatment-related behaviors and the access of patients to sources of information on TB. In the regression multivariate analysis, significant associations with retreatment after loss to follow-up that were detected include: scarce knowledge on tuberculosis, lack of adherence to consultation during the current treatment, noncompliance with follow-up consultation deadline, smoking and HIV negative.Conclusion When compared to controls, cases undergoing TB retreatment after loss to follow-up have less knowledge on the disease, which is a sign for the professionals responsible for health education of the need to invest more time and efforts in activities that help the patient understand the disease and its treatment, as well as to have higher levels of  adherence. In addition, noncompliance with the follow-up consultation deadline, failure to attend consultations during the current treatment and smoking are also factors that may be influenced by poor knowledge on the disease, which leads to the treatment loss to follow-up.